ADVANCING NURSING KNOWLEDGE: AN OVERVIEW OF SAUDI ARABIAN NURSING EDUCATION (CAHIERS MAGELLANES-NS, 2024)
Background: Nursing education in Saudi Arabia has evolved significantly since its inception in 1948, transitioning from male-only diploma programs to a comprehensive array of qualifications, including bachelor's, master's, and doctoral degrees. Despite these advancements, the sector faces multiple challenges, particularly in aligning with the goals set by Saudi Vision 2030. This review identified some key issues from nursing education trends in Saudi Arabia.Method: A search for papers on Google and Google Scholar was done using the topic as the search phrase. Out of 106 papers identified, only 22 were eligible for inclusion in this review.Results & Discussion: Key issues include a high dependency on expatriate nurses, low graduation rates, inadequate skill development, and cultural barriers, particularly for female nurses. Institutional and policy deficits, such as ineffective Saudization policies, a lack of coherent training in evidence-based practice, and fragmented regulatory oversight, further exacerbate these problems. The COVID-19 pandemic has highlighted the need for robust online education platforms and improved healthcare training, with studies indicating a positive yet anxious attitude among nursing students towards e-learning and vaccination. Solutions suggested include streamlining regulatory bodies, enhancing curricula to include critical thinking and problem-solving skills, improving the attractiveness of the nursing profession, and ensuring continuous review of educational policies.Conclusion: This review underscores the necessity for coordinated efforts in policy reform and practical training enhancements to bolster the nursing workforce, thereby meeting the future healthcare needs of Saudi Arabia's growing population.